Senior entrepreneurship and aging in modern business - Sáiz Álvarez, José Manuel; Gámez Gutiérrez, Jorge Alberto (IGI Global, 2020)
""This book explores senior entrepreneurship from the perspectives of economics, sociology, international relations, and ethics"--Provided by publisher"--
Description based on title screen (IGI Global, viewed 01/11/2020)
Keywords: Businesspeople; Entrepreneurship; Older people / Employment; Small business